Relação macho e fêmea e presença de substrato no comportamento reprodutivo de tilápia nilótica (Oreochromis niloticus) - Neves, Bianca Maciel Soares Pimenta (2018)
The reproductive behavior of Nile Tilapia (Oreochromis niloticus) involves the selection of partners for mating and nesting for spawning, with tilapia being a species that exhibits polygyny behavior. The present work tested three male:female (1: 1, 1: 2 and 1: 3) relationships that were equally distributed in the aquariums with and without substrate, totaling 4 replications of these sexual proportions (treatments) in each condition (with and without substrate). For the sexual ratio 1:1 were used 16 animals, the sexual ratio 1:2 24 animals and 1:3, 32 animals, totaling 72 animals in 24 aquariums (60 L). The study had a duration of 21 days, the first 10 to observe the reproductive behavior and the other 11 days to observe the construction of the nests. The observations of the reproductive behavior were made through video cameras and recorded in an etogram that was made from scan sampling, according to the chronological hierarchy of the behaviors, such data were collected according to the method of Altmann (1974), the nests area were quantified and recorded on the 21st day of study. The results were evaluated through analysis of factorial variance, the frequency of occurrence of reproductive behaviors were influenced by the presence of substrate and male: female relationships, as well as, if there was interaction between these factors. The tukey test was used to compare the means of the treatments, with or without the presence of substrate, after which a nest construction analysis was performed. For this analysis, the multiple linear regression model was used to relate the variable area response, with dependent variable relationship. It is concluded that understanding the behavior of different male: female sex relations for the production of Nile Tilapia are important when it comes to reproduction. The relationships showed different behaviors, being the most aggressive the relationship with 1 male and 1 female, but this same sexual relation had a higher demand rate for nest investment, since the sexual relation 1 male and 2 females showed a higher rate of nest construction which may be indicative of courtship between the animals, since the study showed that both male and female construct nests. The nested area correlated with sexual intercourse presented a low correlation which shows that it is not indicative of the parameters reproduction.